Therapy Modalities for Antibody Mediated Rejection in Renal Transplant Patients. (2nd September 2016) - Yilmaz, Vural Taner; Suleymanlar, Gultekin; Koksoy, Sadi; Ulger, Burak Veli; Ozdem, Sebahat; Akbas, Halide; Akkaya, Bahar; Kocak, Huseyin
ABSTRACT: Introduction : The aim of our study was to determine the effectiveness of immunoglobulin, rituximab and plasmapheresis in renal transplant patients with antibody mediated rejection (AMR). Patients and Methods : Fourteen renal transplant patients with AMR were included in this study. The mean age of the patients was 33.9 ± 10.3 years and 10 (71.4%) of them were male. Lymphocyte cross match was negative for all patients and 10 (71.4%) of them were living donor transplants. Six patients were administered tacrolimus, three patients cyclosporine, two patients everolimus, and three patients sirolimus for immunosuppression. The patients with AMR were administered IVIG, rituximab and plasmapheresis. Results : Patient survival rate was 100%, graft survival rate after AMR was 50% in the first year and 33% in the 2nd and third years. AMR developed 31.9 ± 25.9 months after transplantation. Seven (50%) patients lost their grafts. Delayed graft function was observed in 28.6%, chronic allograft dysfunction in 78.5%, diabetes after transplantation in 14.3%, and cytomegalovirus infection in 7.1% of the patients. At the last follow-up, the mean blood creatinine was 3.1 ± 1.4, the mean proteinuria was 2300 (1300–3300) mg/day and the mean GFR was 34.5 ± 17.6 ml/min. C4d was positive in peritubullar capillaries in all patients, while neutrophil accumulation in peritubular and glomerular capillaries was observed in 8 patients. Chronic allograft vasculopathy was observed in 12 patients. Conclusion : AMR leads to progressive loss of renal function and has low graft survival. More effective treatment alternatives are needed for this clinical issue.